Samira Saramo, Building That Bright Future: Soviet Karelia in the Life Writing of Finnish North Americans - Lynn Domina (European Journal of Life Writing)
In Building That Bright Future: Soviet Karelia in the Life Writing of Finnish North Americans, Samira Saramo has written an interesting and clear study of a significant but little-known series of events in world history. During the late 19th and early 20th centuries, over 300,000 Finns immigrated to the United States and Canada, often settling in Michigan’s Upper Peninsula and northern Wisconsin and Minnesota. During the early 1930s, many of these immigrants were actively recruited to return, not to Finland proper but to Karelia, a frequently-disputed region on the border of Finland and what was then the Soviet Union. Many of these Finns tended politically toward socialism and perceived the Soviet Union as a favorable sign of the kind of future they believed in. Simultaneously, they were attractive to members of the Karelian leadership because they were more educated than most residents of the region and were assumed to have greater access to tools, machinery, and other financial resources. Eventually, about 6500 North American Finns moved to Karelia, where they were met with significant social and physical challenges. Many of them eventually died during the Stalinist Great Terror.